2020
DOI: 10.24036/jkmb.10988800
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh gaya kepemimpinan struktur inisiasi, subjektif diagnostik, subjektif interaktif terhadap keadilan evaluasi

Abstract: This study aims to examine the effect of initiation structure leadership on evaluation fairness. This study also examines the mediation of subjective diagnostic and subjective interactive on the relationship between initiation structure leadership and evaluation fairness. The population and sample this study use subordinates in service, merchandising and manufacturing business. Data were collected using a questionnaire with hand delivery system technique and processed using structural equation modeling with Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…Particularly in organizations such as LPD, failures to implement MCS could be traced to leadership roles leading to deviations in management. Hernando et al (2022) indicated that levers of control could influence the association between performance measurement and managerial performance. Consequently, the below hypothesis was proposed based on the findings.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Particularly in organizations such as LPD, failures to implement MCS could be traced to leadership roles leading to deviations in management. Hernando et al (2022) indicated that levers of control could influence the association between performance measurement and managerial performance. Consequently, the below hypothesis was proposed based on the findings.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Dinamika perekonomian yang semakin maju di era globalisasi saat ini mendorong para pelaku usaha untuk dapat bersaing di tengah persaingan (Afrizal et al, 2020a;Firdaus et al 2023;Hernando, 2020;Neldawaty dan Hernando, 2021;Rafiqi et al 2022; Berbagai strategi dilakukan telah dirumuskan oleh pimpinan dan jajaran organisasi untuk dapat mencapai visi, misi, tujuan dan sasaran yang telah ditetapkan (Hernando et al 2022;Hernando, Abdurrahman dan Prasetyo, 2020;Hernando, Prasetyo dan Abdurrahman, 2020). Pelaku bisnis didorong untuk transparan kepada publik (Adriani et al 2023;Junaidi et al 2022;Prajanto, 2020).…”
Section: Pendahuluanunclassified
“…Kinerja usaha merupakan gambaran mengenai pencapaian pelaksanaan suatu program kegiatan atau kebijakan dalam mewujudkan sasaran, tujuan, visi dan misi organisasi yang dituangkan melalui perencanaan strategis suatu organisasi (Sidiqqoh dan Alamsyah, 2017). Pengukuran kinerja usaha ini dibagi menjadi dua faktor yaitu finansial dan non finansial (Hernando et al, 2022). Pengukuran kinerja non finansial dilihat dari keberhasilan perusahaan mencapai tujuannya, sedangkan kinerja finansial diukur berdasarkan faktor-faktor semisal pertumbuhan penjualan atau ROI (Tarutė dan Gatautis, 2014).…”
Section: Pendahuluanunclassified